Effect of metals on Daphnia magna and cladocerans representatives of the Argentinean Fluvial Littoral - Regaldo, Luciana María (2014)
Chronic toxicity tests were conducted to assess the effect of Cu, Cr and Pb on Moinodaphnia macleayi and Ceriodaphnia dubia -two cladoceran species from the Argentinian Fluvial Littoral Zone (AFLZ)- and Daphnia magna -an holarctic species-. The specimens were exposed to three concentrations of each metal. As endpoints, the number of living and dead organisms, molts, neonates released, and the age of first reproduction were recorded. Chronic assays showed that Cu significantly affected the analyzed life history traits in the three species. The lowest Pb and Cr concentrations did not affect survival, molting or fecundity in D. magna. Conversely, in M. macleayi and C. dubia, survival, molting and fecundity showed highly significant differences in all the concentrations tested compared to control assay. The present study stresses the importance of using biological parameters as bioindicators, as well as the study species from the Southern Hemisphere to assess metal pollution.